DAMPAK LAJU DEFORESTASI TERHADAP HILANGNYA KEANEKARAGAMAN HAYATI DI INDONESIA - Ardhana, I Putu Gede (Metamorfosa: Journal of Biological Sciences; Vol 3 No 2 (2016)DO - 10.24843/metamorfosa.2016.v03.i02.p09, 2016)
The purpose of this study was to examine the impact of deforestation on biodiversity loss in Indonesia. Firstly author presented information about deforestation trends that spread across Indonesia. And presented information about forest fires that triggered off the continuous deforestation and occurred one after another throughout the year. The collected data showed deforestation and forest fires have occurred since 1960 to 2015, and deforestation and forest fires implicated in the extinction of species diversity, genetics, and ecosystems that spreads from Sunda region to Sahul region.  Author used descriptive regulation and legislation methods, used literature approach, as well as arranged with descriptive and interpretational form in papers. From the results of this study author concluded that deforestation rate implicates in forest fires that occur continuously throughout the year and can not be inevitable possibility of extinction of biodiversity spread across Indonesia.
Keywords: impact, deforestation, forest fires, biodiversity loss